2014
DOI: 10.1002/2013jf002985
|View full text |Cite
|
Sign up to set email alerts
|

Late Quaternary incision rates in the Vésubie catchment area (Southern French Alps) from in situ-produced36Cl cosmogenic nuclide dating: Tectonic and climatic implications

Abstract: We have estimated recent river incision rates using the in situ-produced 36 Cl cosmogenic nuclide concentrations. The target site consists of a~25 m high vertical profile along a polished river cliff located in Jurassic limestones in the Vésubie catchment area, in the southern French Alps. The 36Cl exposure ages of the sampled river polished surface range from 3 to 14 ka, i.e., after the Last Glacial Maximum. Our data suggest as a first approximation a linear age/height relationship and lead to a mean incis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 70 publications
1
39
0
Order By: Relevance
“…The study area is located in the Argentera-Mercantour massif (southwest Alps) along the upper Tinée Valley (Figure 1) where climatic fluctuations, and in particular the chronology of glacier retreat since the LGM, have been investigated by several studies (Bigot-Cormier et al, 2005;Sanchez et al, 2010a;Darnault et al, 2012;Saillard et al, 2014;Brisset et al, 2015;Rolland et al, 2017). 394 Y. ROLLAND ET AL.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The study area is located in the Argentera-Mercantour massif (southwest Alps) along the upper Tinée Valley (Figure 1) where climatic fluctuations, and in particular the chronology of glacier retreat since the LGM, have been investigated by several studies (Bigot-Cormier et al, 2005;Sanchez et al, 2010a;Darnault et al, 2012;Saillard et al, 2014;Brisset et al, 2015;Rolland et al, 2017). 394 Y. ROLLAND ET AL.…”
Section: Study Areamentioning
confidence: 99%
“…Figure 12). Subsequent installation of modern denudation and fluvial incision in low valleys is also constrained at that time period by CRE dating of polished river surfaces, which highlight onset of fluvial erosion at 19-22 ka, and transient erosional events involving incision rates >10 mm yr À1 at~14 and~11 ka (Saillard et al, 2014;Rolland et al, 2017;Petit et al, 2017). Subsequent installation of modern denudation and fluvial incision in low valleys is also constrained at that time period by CRE dating of polished river surfaces, which highlight onset of fluvial erosion at 19-22 ka, and transient erosional events involving incision rates >10 mm yr À1 at~14 and~11 ka (Saillard et al, 2014;Rolland et al, 2017;Petit et al, 2017).…”
Section: Permanence Of Debris Covered Glaciers After the Younger Dryamentioning
confidence: 99%
“…In compressional forearc settings, near‐surface fault expressions are often blind, associated with folded Quaternary sediments or abrupt changes in topography. In turn, river incision rates can be interpreted as fault uplift rates [ Hall et al , ; Alvarado et al , ], but this requires taking into account the effects of both climate variations and transient processes that remain mostly unknown [e.g., Saillard et al , ; Rolland et al , ]. Globally, only a few cases exist for which precise fault slip rates have been successfully determined by direct dating of a fault scarp [e.g., Jackson et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have argued that records of tectonic activity are limited to Andean forearc landscape features of southern Peru [e.g., Sébrier et al, 1985]; however, more recent studies have not only shown that active structures exist and accommodate relief growth but have also suggested that rates based on dated offset geomorphic features should also be considered in models of recent forearc deformation [e.g., Hall et al, 2012]. fault uplift rates [Hall et al, 2012;Alvarado et al, 2014], but this requires taking into account the effects of both climate variations and transient processes that remain mostly unknown [e.g., Saillard et al, 2014;Rolland et al, 2017]. Globally, only a few cases exist for which precise fault slip rates have been successfully determined by direct dating of a fault scarp [e.g., Jackson et al, 2002].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are a few case studies that reported river incision rates, such data stem either from steep bedrock gorges Saillard et al, 2014), from high-relief areas that have attained threshold hillslopes (Himalaya; Burbank et al, 1996;Taiwan;Schaller et al, 2005), or from regions that were completely covered by ice during the last glaciation (Reusser et al, 2004). Unfortunately, there currently seems to be no region where both an accurate incision rate as well as local and catchment-wide 10 Be denudation rates are available.…”
Section: Validation Of New Approach and Potential Improvementsmentioning
confidence: 99%